Graphene nanoribbon winding around carbon nanotube; Computational Materials Science; Vol. 135 - Savin A. V. Aleksandr Vasiljevich; Korznikova E. A. Elena Aleksandrovna; Dmitriev S. V. Sergey Vladimirovich; Soboleva E. G. Elvira Gomerovna (2017, 2017)
Title screen